Spatial Analytics of Climate Change Impacts: The Case Study of Maribor - Blaj, Oana Iulia Maria; Budzan, Łucja; Cakaj, Mirlinda; Đurović, Luka; Hocková, Eliška; Kolukaj, Lediona; Krász, Márton; Ivajnšič, Danijel (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
Climate change represents one of the most pressing challenges of the twenty-first century, marked by rising global temperatures, more frequent heatwaves, and increasing risks of floods and droughts. Urban areas are particularly vulnerable because dense construction, limited vegetation, and impervious surfaces intensify heat exposure and reduce resilience. This urban heat island effect has significant consequences for human health, infrastructure, and the environment, making cities critical focal points for adaptation strategies. This study explores long-term climate change in Slovenia with a focus on Maribor, the country’s second-largest city. Maribor’s geographical location in the Drava valley, combined with its ageing population, increases its vulnerability to extreme heat events. Evidence indicates a seasonal shift in urban heat intensity from colder to warmer months, with projections of substantial increases in future decades, particularly in industrial zones. By combining high-resolution climate data, satellite imagery, and socio-demographic indicators, this research identifies spatial patterns of heat stress and highlights vulnerable areas. The findings provide a scientific basis for sustainable urban planning and effective adaptation to climate change.